(untitled) (The Review of Diabetic Studies, 2025)
Crisis situations, whether caused by natural disasters, armed conflicts, pandemics, or mass-casualty accidents, present critical challenges to healthcare systems, particularly in managing injuries. Emergency Medical Services (EMS) serve as the frontline of response, bridging the gap between the site of injury and hospital-based care. This review explores the effectiveness of EMS in managing injuries during crises, synthesizing evidence on their role in triage, stabilization, transport, and coordination within disaster response frameworks. We highlight key practices such as pre-hospital interventions, advanced life support, and deployment of mobile medical units. Furthermore, the review identifies factors that influence EMS effectiveness, including training, resource availability, communication systems, and integration with other emergency responders. While EMS has demonstrated substantial impact in improving survival and reducing morbidity during crises, challenges persist in resource-limited settings, overwhelmed systems, and underdeveloped disaster preparedness plans. The article also discusses innovative approaches such as telemedicine integration, AI-assisted triage, and cross-border collaborations that can enhance EMS performance. Finally, recommendations are provided to strengthen EMS systems globally, ensuring readiness for future crises.